2020
DOI: 10.1111/jpc.14720
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric constipation for general paediatricians: Review using a case‐based and evidence‐based approach

Abstract: Constipation is a common problem in childhood. The most common type of constipation is functional, accounting for 90–95% of all cases. The aim of this review is to provide clinical scenarios with treatment using evidence‐based information, and management strategies and a clinical algorithm to guide the management of constipation in children. Recent guidelines and online information sites are detailed. Clinical red flags and organic causes of constipation are included. Four clinical scenarios are presented: cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…A previous study showed that large and hard stool was the most frequent symptom among children with functional constipation, hard stool consistency was found in about 93.7% of cases ( 41 ). In the diagnosis of FC and identification of early warning symptoms ( 42 ), parental perception of constipation depends primarily on stool traits and frequency of defecation, which is also the most common reason for seeking medical attention. This suggested that parents were more likely to ignore other symptoms, leading to delays in seeking medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that large and hard stool was the most frequent symptom among children with functional constipation, hard stool consistency was found in about 93.7% of cases ( 41 ). In the diagnosis of FC and identification of early warning symptoms ( 42 ), parental perception of constipation depends primarily on stool traits and frequency of defecation, which is also the most common reason for seeking medical attention. This suggested that parents were more likely to ignore other symptoms, leading to delays in seeking medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CPGs in algorithmic form is very common for the appropriate assessment and care for many pathological conditions, both in adulthood and in childhood. Especially in childhood, many CPGs are presented in the format of an algorithm, either for the diagnosis of a variety of disorders, such as inborn anomalies of metabolism 61 , or the management of several conditions, such as constipation 62 . However, to the best of our knowledge, although CPGs for nutrient intake and nutrient-related chronic metabolic conditions are well established in the literature, this work is the first one that summarizes and presents them in algorithmic form, in order to further increase their adoption in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, approximately 40% of children with functional constipation develop symptoms of constipation in the early years of life. 5 Regarding the close link between childhood constipation and thyroid disorders, practical-clinical guidelines released by the North American Society of Gastroenterology, Liver, and Nutrition recommend that thyroid hormone testing should be performed in children with severe and refractory constipation and that most patients should be screened before referring to a pediatric gastroenterologist. The diagnosis of hypothyroidism should be also considered in the differential diagnosis of constipation.…”
Section: Introductionmentioning
confidence: 99%